2019
DOI: 10.1038/s41598-019-54203-0
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon deep sequencing improves Plasmodium falciparum genotyping in clinical trials of antimalarial drugs

Abstract: Clinical trials monitoring malaria drug resistance require genotyping of recurrent Plasmodium falciparum parasites to distinguish between treatment failure and new infection occurring during the trial follow up period. Because trial participants usually harbour multi-clonal P. falciparum infections, deep amplicon sequencing (AmpSeq) was employed to improve sensitivity and reliability of minority clone detection. Paired samples from 32 drug trial participants were Illumina deep-sequenced for five molecular mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 30 publications
1
66
0
Order By: Relevance
“…Nevertheless, the results from this study showed a substantial improvement in sensitivity for detecting minor parasite populations in a sample, particularly those above 5% proportion, with acceptable precision. While deep sequencing of individual targeted antigenic genes also provides ability to detect gene-specific minor variants in a sample, the estimates in the highly selected genes might not represent true genomic signatures of parasites [ 14 , 15 , 37 ] and may offer limited temporal and geographic discrimination between parasite populations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the results from this study showed a substantial improvement in sensitivity for detecting minor parasite populations in a sample, particularly those above 5% proportion, with acceptable precision. While deep sequencing of individual targeted antigenic genes also provides ability to detect gene-specific minor variants in a sample, the estimates in the highly selected genes might not represent true genomic signatures of parasites [ 14 , 15 , 37 ] and may offer limited temporal and geographic discrimination between parasite populations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common genotyping method is to PCR amplify microsatellite markers or polymorphic genes, such as the msp family, the size of the resulting amplicon(s) being variable between different isolates [ 1 ]. Amplicon ultra-deep sequencing now allows multiplexing samples and are particularly useful to determine the proportion of each strain in infections with multiple genotypes [ 2 ]. Alternatively, genotyping a few dozen single nucleotide polymorphisms (SNPs) generates a molecular barcode specific to each isolate.…”
Section: Genotyping Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 23, 2021. ; https://doi.org/10.1101/2021.03.23.436602 doi: bioRxiv preprint allelic diversity obtained from (15). We use the first three markers by default but also included the less diverse markers csp and msp-7 in our simulations as these may be used when other markers fail to amplify (15) and allows us to evaluate whether increasing the number of Ampseq markers would significantly improve accuracy.…”
Section: Genetic Diversity Of Infections At Treatment Is Termed the Mmentioning
confidence: 99%
“…AmpSeq methods are well established in the wider malarial context for tracking specific genes (e.g., for drug resistance) within populations (11)(12)(13), and for evaluating the efficacy of the RTS,S/AS01 vaccine (14). AmpSeq as a method to genotype malaria parasites in clinical trials is relatively novel (15) and, despite its putative advantages, has not yet been used as the primary genotyping endpoint for a clinical trial or TES (although it has been used to reanalyze archived blood samples (15)).…”
mentioning
confidence: 99%